Evaluation of α-Glucosidase Inhibitory Effect of 50% Ethanolic Standardized Extract of Orthosiphon stamineus Benth in Normal and Streptozotocin-Induced Diabetic Rats - Mohamed, Elsnoussi Ali; Ahmad, Mariam; Lee, Fung Ang; Asmawi, Mohd. Zaini; Mun, Fei Yam (Hindawi Publishing Corporation, 2015)
In the present study, a 50% ethanolic extract of Orthosiphon stamineus was tested for its α-glucosidase inhibitory activity. In vivo assays of the extract (containing 1.02%, 3.76%, and 3.03% of 3′hydroxy-5,6,7,4′-tetramethoxyflavone, sinensetin, and eupatorin, resp.) showed that it possessed an inhibitory activity against α-glucosidase in normal rats loaded with starch and sucrose. The results showed that 1000 mg/kg of the 50% ethanolic extract of O. stamineus significantly () decreased the plasma glucose levels of the experimental animals in a manner resembling the effect of acarbose. In streptozotocin-induced diabetic rats, only the group treated with 1000 mg/kg of the extract showed significantly () lower plasma glucose levels after starch loading. Hence, α-glucosidase inhibition might be one of the mechanisms by which O. stamineus extract exerts its antidiabetic effect. Furthermore, our findings indicated that the 50% ethanolic extract of O. stamineus can be considered as a potential agent for the management of diabetes mellitus.